A Simplified Systematic Literature Review: Improving Software Requirements Specification Quality With Boilerplates - Umairah, Anuar; Sabrina, Ahmad; Nurul Akmar, Emran (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2015)
The quality of Software Requirements Specification (SRS) is crucial in order to ensure successful project completion. SRS of poor quality usually lacks of quality attributes such as completeness, accuracy and disambiguity. Boilerplate is a technique used to deal with problems in SRS. However, study on the coverage of boilerplate ' s contribution especially in improving SRS quality is limited. This paper presents Systematic Literature Review (SLR) on problems in SRS and boilerplates. The review that covers literature from 1997 to 2015 reveals that I) poor quality SRS is the most popular problem among the other five SRS problems discovered, 2) Boilerplate technique has been applied to cope with SRS of poor quality, where disambiguity has been found the most popular quality attribute.